Comparison of kinematic parameters and muscle activation patterns in alpine skiers training on two types of training devices - Woznica, W.; Zawadzki, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
The role of the training devices dedicated to alpine skiers is not only to improve their lower limbs' muscle strength, but also to develop the sense of balance, coordination of movements and muscle power, which are crucial for the skiers' on-snow performance. The aim of the present study was to compare with each other: the kinematic parameters of movement and the electrical activity of five muscle groups in lower limbs bilaterally during exercising on two different training platforms and skiers' results of the on-snow performance reported in literature (Hraski & Hraski 2009, Panizzolo et al. 2010). A Significant question to be also answered is if the performance on these platforms was similar enough to the skiing characteristics that calling them 'simulators' would be fully justified? (Spitzenpfeil et al. 2005).